Cultural Values in Javanese Proverbs: An Ecolinguistic Study of Flora And Fauna Metaphors - Nadiya Yunianti; Mon Karlo Mangaran; Mahoor Nisar (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to examine how cultural values are represented through flora and fauna metaphors in Javanese proverbs from an ecolinguistic perspective, with particular attention to how natural elements are used to convey cultural wisdom and human–nature relationships in Javanese society. Methodology: The study employs a descriptive qualitative design with an ethnographic approach. The data consist of 30 selected Javanese proverbs taken from Paribasan Jawa by Johan Argono, comprising 15 proverbs containing flora metaphors and 15 containing fauna metaphors. Main Findings: The findings reveal that flora and fauna metaphors in Javanese proverbs primarily reflect cultural values related to morality, social relationships, and life guidance. Flora metaphors tend to emphasize ontological meanings, while fauna metaphors more frequently employ structural metaphors to convey social behavior and moral lessons. Novelty/Originality of this study: The novelty of this study lies in its ecolinguistic analysis of Javanese proverbs through a focused examination of flora and fauna metaphors. By highlighting how local ecological symbols encode cultural wisdom, the study contributes to discussions on language, culture, and environmental awareness, particularly in the context of preserving local knowledge and traditional values.